2019
DOI: 10.1111/dom.13738
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility of patients with type 2 diabetes for sodium‐glucose co‐transporter‐2 inhibitor cardiovascular outcomes trials: An assessment using the Diabetes Collaborative Registry

Abstract: Generalizability of findings from cardiovascular outcomes trials (CVOTs) to patients with type 2 diabetes (T2D) in clinical practice is unknown. We assessed the proportions of patients in the Diabetes Collaborative Registry who would have met enrolment criteria for pivotal CVOTs of sodium‐glucose co‐transporter‐2 inhibitors (SGLT‐2is): EMPA‐REG OUTCOME, CANVAS, DECLARE and VERTIS CV. In 172 643 patients, mean [standard deviation (SD)] age and HbA1c were 68.1 (11.8) years and 7.8% (2.2), respectively; 56.8% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Similar analyses have been performed on CVOTs for SGLT‐2is . Nicolucci et al 11 showed that real‐world T2D patients eligible for CVOTs on SGLT‐2is were different to trial populations in many instances .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar analyses have been performed on CVOTs for SGLT‐2is . Nicolucci et al 11 showed that real‐world T2D patients eligible for CVOTs on SGLT‐2is were different to trial populations in many instances .…”
Section: Discussionmentioning
confidence: 87%
“…A few studies have examined what proportion of T2D patients from various clinical care settings would satisfy I/E criteria to be enrolled in specific CVOTs, but no study to date has examined what the proportion is of real‐world patients that corresponds to CVOT populations. Indeed, applying CVOT enrolment criteria to real‐world T2D patients yields subgroups that are substantially different from the actual CVOT populations, thereby leaving the question of generalizability unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to recognize the differences in eligibility criteria when considering the applicability of these results to the usual care of T2D patients. In 172 643 patients from the Diabetes Collaborative Registry, for example, the proportion of patients eligible for CVOTs ranged from 26% (EMPA‐REG OUTCOME) to 44% (DECLARE) and 48% of patients were ineligible for all CVOTs …”
Section: Cardiorenal Outcomes From Cardiovascular Outcome Trialsmentioning
confidence: 99%
“…The arrow indicates reduced risk; the symbol "=" indicates neutrality the usual care of T2D patients. In 172 643 patients from the Diabetes Collaborative Registry, for example, the proportion of patients eligiblefor CVOTs ranged from 26% (EMPA-REG OUTCOME) to 44% (DECLARE) and 48% of patients were ineligible for all CVOTs 35. THE NEAR FUTUREThe near future is likely to bring new insights to the therapeutic strategy for T2D.…”
mentioning
confidence: 99%
“…Interestingly, a high proportion of patients initiating dapagliflozin in routine clinical practice satisfied DECLARE-TIMI 58 enrolment criteria. For comparison, Wittbrodt et al reported that the eligibility of patients in the Diabetes Collaborative Registry was much lower for other CVOTs with SGLT2i, thereby suggesting a higher generalizability of the DECLARE-TIMI 58 population in the southern European population [25]. However, it should be noted that, even among patients who satisfied DECLARE-TIMI 58 eligibility criteria and received dapagliflozin, significant differences were found compared to the actual DECLARE-TIMI 58 population.…”
Section: Discussionmentioning
confidence: 99%